Design, analysis and fabrication smart vacuum cleaner / Alif Amaluddin - Amaluddin, Alif (2022)
Smart vacuum cleaner is the product that has been choose for this final year project. Doing some research about vacuum cleaner and learn about how does the vacuum cleaner work. Moreover, the vacuum cleaner has their own problem and always has the same main problem. The problem on vacuum cleaner need to be solved. From the survey and article that have been conducted, the problem can be confirm. The objective can be made to solve the problem by doing design, analysis and fabricate using the good material and part inside of the vacuum cleaner. By using the Solidwork the sketch and the part can be made with true dimension and calculation. Solidwork also will help us on doing analysis the part that hold a lot of forces. By using the analysis we can find the stress, displacement and torque. Then on next part we choose the good part with good price to be inside the project. Then, the vacuum cleaner part need to fabricate to put part in the vacuum cleaner. By the end of the work that have been done, the vacuum cleaner can be produce and will be much functional than before. The objective and significant of this project will be obtained.